DNA Barcoding of Freshwater Eels Anguilla spp from Kuari River Based on Cytochrome C Oxidase Subunit I (COI) Gene - Maulidya, Ainayyah; Syaifudin, Mochamad; Wijayanti, Marini (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract Highlight Research Freshwater eels in Kuari River consisted of two species marmorata and A. bengalensis Anguilla marmorata had the highest similarity of 99.82%-100%, while bengalensis indicated the highest identity of 99.84%-100% to the same species in the GenBank database. Phylogenetic species indicated that Anguilla marmorata and Anguilla bengalensis form two different sub-clusters. The water quality in the Bengkulu Kuari River were still in tolerance for fish growth and survival.     Abstract Freshwater eels (Anguilla spp.) are classified in the family Anguillidae, and included in the catadromous group. This study aimed to determine the COI gene sequences of the mitochondrial DNA, analyze the genetic distances, and phylogenetics, and characterize the physical and chemical parameters of between freshwater eels habitat in the Kuari River Bengkulu. This research was conducted from November 2020 – April 2021. The methods used in barcoding eel species were DNA isolation, DNA amplification using PCR (Polymerase Chain Reaction), electrophoresis, and sequencing of COI gene regions in mtDNA. The COI mtDNA gene fragments were obtained from PCR results with an annealing temperature of 50°C for 30 seconds in 35 cycles. BLASTn analysis of eel samples AM3 and AM4 had the highest similarity of 99.82%-100% to Anguilla marmorata, and samples AB2-AB5 indicated the highest identity of 99.84%-100% to Anguilla bengalensis. Phylogenetic species indicated that Anguilla marmorata and Anguilla bengalensis form two different sub-clusters. The water qualities in the Bengkulu Kuari River were temperatures 26.5-27.5oC, pH 7.1-8.7, dissolved oxygen 6.19-9.54 mg L-1, brightness 21-47 cm, ammonia 0.16-0.41 mg L-1, total alkalinity 20–52 mg L-1, TDS 33–49 mg L-1, salinity 0.3-0.4 ppt and water velocity 0.5-0.8 ms-1. The COI gene in DNA barcoding is very appropriate to be used for the identification of Anguilla spp species by comparing the DNA sequence of the COI gene with the existing database in the Genbank.